A shallow-water cyrtocrinid crinoid (Articulata) from the upper Albian of the Western Pyrenees, North Spain. (June 2022) - Zamora, Samuel; López-Horgue, Mikel A.
Abstract: The cyrtocrinid crinoid Proholopus holopiformis (Remeš, 1902) is described from the upper Albian succession that may be included in the Albeniz unit to the east of Iruñea-Pamplona (Navarre, Western Pyrenees, Spain). Although based on partially disarticulated material, this taxon preserve calyx, stem, attachment structure, and brachial plates from the arms. Proholopus holopiformis was previously described from the Upper Jurassic-Lower Cretaceous of the Czech Republic and Lower Cretaceous of France and Crimea, thus the occurrence from Spain represents the youngest of the species. This allows a better characterization of the family Proholopodidae that was originally described based on calyx morphology only and expands its distribution to the upper Albian. Proholopus holopiformis inhabited the fore-reef areas of coral-sponge bioconstructions. Based on coral types, crinoids are thought to have dwelled near the euphotic-oligophotic zones transition and, thus, thrive in shallow depths. Most specimens have bite marks compatible with cidaroid predation. This represents one of the youngest occurrences of cyrtocrinids inhabiting shallow marine environments before their migration to the deep sea due to the ongoing Mesozoic Marine Revolution. Highlights: A cyrtocrinid crinoid is described from the upper Albian of Spain. Proholopus holopiformis is based on cups, stems, brachials, and holdfast allowing a well understanding of its morphology. Sedimentological analysis suggest that P. holopiformis lived in shallow water conditions less than 50 m deep. All analyzed specimens show external marks in the calyx compatible with predation by cidaroid echinoids. This represents one of the youngest occurrence of cyrtocrinid crinoids in shallow marine environments.